Integrating network pharmacology, molecular docking, and animal studies to investigate the protective effect of astragalus polysaccharide on fluoride-induced renal injury in rats - Xiaoyue Zhang; Qianda Yan; Yuanyuan Xiao; Xingyan Du; Xuehua Zhang; Didong Lou; Fang Peng; Daiyong Chen; Wenchao Tang (Ecotoxicology and Environmental Safety)
Fluoride is an essential trace element required for normal physiological functions and holds significant importance for human health. However, excessive fluoride intake can lead to renal damage, for which effective prevention and therapeutic strategies remain scarce. Astragalus polysaccharide (APS), a major bioactive component of the traditional Chinese herb Astragalus membranaceus, possesses pharmacological properties including anti-inflammatory, antiviral, and antioxidant activities. In this study, we investigated the protective effects of APS against fluoride-induced renal injury in vivo experiment. Additionally, network pharmacology and molecular docking techniques were employed to predict its potential mechanisms of action, while the protein expression levels of key target molecules were validated. The results demonstrated that APS intervention significantly alleviated renal injury and oxidative stress induced by sodium fluoride (NaF) in rats. Key targets involved in the amelioration of fluoride-induced renal damage by APS included STAT3, Caspase-3, JUN, MMP1, and PTGS2. Molecular docking analysis revealed high-affinity binding between APS and these core targets. Immunohistochemical and Western blot analysis further confirmed that APS suppressed the expression of pro-apoptotic proteins STAT3, Caspase-3, JUN, and MMP1 while enhancing the expression of the anti-apoptotic protein PTGS2. Overall, our findings suggest that APS alleviates fluoride-induced renal injury by modulating multiple targets, with the potential mechanism linked to the regulation of apoptotic processes. This study provides a theoretical basis for the prevention and treatment of fluoride toxicity.